69.2k views
0 votes
2(11-k)=-4(k+4) can you please give me the answer i dont care if there is no work just want answer

2 Answers

4 votes

Answer:

-19

Explanation:

2(11 - k) =-4(k +4)

22 - 2k =-4k - 16

-2k +4k =-16 - 22

2k =-38

k=-38 :2

k=-19

User Sargam Modak
by
6.1k points
4 votes

Answer:

The answer to this is -19.

This is the answer because After you distribute, You should have:

22-2k=-4k-16

Then you Add 2k to both sides. then you get this:

22=-2k-16

Then you Add 16 to both sides. Then you get this:

38=-2k

Then you divide both sides by -2. And you get:

-19

User YaDav MaNish
by
5.6k points